Examination of the importance of anger/irritability and limited prosocial emotion/callous-unemotional traits to understand externalizing symptoms and adjustment problems in adolescence: A 10-year longitudinal study - Urben, Sébastien; Habersaat, Stéphanie; Palix, Julie; Fegert, Jörg M.; Schmeck, Klaus; Bürgin, David; Seker, Süheyla; Boonmann, Cyril; Schmid, Marc (Frontiers in Psychiatry, 2022)
Objective: Within a longitudinal study (10-year follow-up), we aim to examine the role of anger/irritability and limited prosocial emotion/callous-unemotional traits in predicting externalizing symptoms and adjustment problems in individuals formerly in youth residential care institutions. Method: These dimensions were assessed in 203 young adults, with baseline assessments during youth residential care and a follow-up 10 years later. Results: Emotional problems and psychopathological symptoms reduced over time. A younger age at baseline, anger/irritability both at baseline assessment and regarding their aggravation over time predicted the level of externalizing symptoms 10 years later (R2=.431), but also predicted externalizing symptoms worsening over time (R2=.638). Likewise, anger/irritability predicted the level of adjustment problems at follow-up (R2=.471) and its worsening over time (R2=.656). Discussion: Our results suggest that dysregulation of anger/irritability is a key factor in the prediction of long-term externalizing symptoms and adjustment problems as well as its worsening over time. Possible implications for intervention and prevention are discussed.